К определению температурных режимов работы гидрообъемной передачи в составе бесступенчатой гидрообъемно-механической трансмиссии колесного трактора - Самородов, Вадим Борисович; Шевцов, Вадим Михайлович (Consilium Sp. z o.o., 2016)
В статье представлен анализ способов определения и методов описания температурных режимов на различных участках гидрообъемной передачи в составе бесступенчатых трансмиссий тракторов. Предложены методики для определения температур в гидрообъемных передачах в составе двухпоточных гидрообъемно – механических трансмиссий тракторов с учетом их конструктивных и эксплуатационных характеристик. В статье обоснована необходимость выполнения предварительного анализа кинематических и силовых характеристик трансмиссии с целью определения потоков мощности, проходящих через гидрообъемную передачу.

The article presents an analysis of ways to define and describe the methods of temperature regimes in different parts of hydrostatic transmission as part of a continuously variable transmission tractors. The techniques for determining the temperature in the hydrostatic transmission as part of double-split hydrostatic - mechanical transmissions of tractors with regard to their design and performance. The article substantiates the necessity of performing a preliminary analysis of kinematic and power characteristics of the transmission to determine the power flows through hydrostatic transmission. To solve this problem were analyzed works devoted to the description of the definition of working fluid temperature in different parts of hydraulic systems, taking into account features of their design and operating conditions as a part of machine - tractor unit. The article presents examples of the schematic description of the temperature distribution of the working fluid in different parts of hydrostatic transmission and the point of mixing of different temperature flows. Also provided according to describing the working fluid temperature, depending on their physical properties and operating conditions of the transmission. The article substantiates the recommendation for joint determination of kinematic, force and temperature characteristics of a continuously variable transmission using a description of the whole complex of mathematical models in the form of a matrix.
Temperature operation of hydrostatic transmission as part hydrostatic-mechanical transmissions of wheeled tractors of general purpose
Keywords: трансмиссия бесступенчатая; передача гидрообъемная; режим температурный; характеристики эксплуатационные; continuously variable transmission; hydrostatic transmission; temperature control